Pengamalan Nilai-Nilai Pancasila Bagi Generasi Milenial - Devi Anggraini; Fauzal Fathari; Jordi Wahyu Anggara; Muhammad Devon Ardi Al Amin (Universitas Islam Malang, 2020)
This writing is motivated by the attitude that is seen about the appreciation of the values of Pancasila which began to dissapear. Writing is based on today’s life where people, especially millenials, began to shift the life guidelines from Pancasila. The results seen in the current life environment, shifts in the application of Pancasila values have long occurred and gradually increasingly alarming in line with the progress of science and technology. Individual attitudes are more visible than social with others. But there are also some who still socialize with others through joint discussions in a forum. The purpose of writing this scientific journal is to re-apply the values contained in Pancasila in the current millenial life.